Effects of kinesio taping on tuck jump performance in competitive male athletes - Sheikhi, B.; Letafatkar, A.; Marchetti, P. H.; Eftekhari, F.; Wallace, B. J.; Maselli, F.; Rossettini, G.; Granacher, U.; Zouhal, H. (International Journal of Sports Medicine, 2023)
This study aimed to measure the acute effects of kinesio taping at different stretches on tuck jump performance in active individuals. Seventy-five males (23.01±2.24 years, 178.35±8.12 cm, 72.47±6.58 kg) were randomly distributed into three groups: (1) kinesio taping without stretch, (2) kinesio taping with approximately 50% stretch, and (3) kinesio taping with approximately 75% stretch. The tuck jump performance of all participants was determined at baseline, immediately after applying kinesio taping, and 24 and 72 hours later. The participants` tuck jump performance did not improve immediately after the kinesio taping application, 24 hours, and 72 hours after the application. No significant differences were found between the kinesio taping groups at any time point (p>0.05). This study demonstrated no effects of kinesio taping on neuromuscular performance.